2014
DOI: 10.7554/elife.01963
|View full text |Cite
|
Sign up to set email alerts
|

Atomic model of the F420-reducing [NiFe] hydrogenase by electron cryo-microscopy using a direct electron detector

Abstract: The introduction of direct electron detectors with higher detective quantum efficiency and fast read-out marks the beginning of a new era in electron cryo-microscopy. Using the FEI Falcon II direct electron detector in video mode, we have reconstructed a map at 3.36 Å resolution of the 1.2 MDa F420-reducing hydrogenase (Frh) from methanogenic archaea from only 320,000 asymmetric units. Videos frames were aligned by a combination of image and particle alignment procedures to overcome the effects of beam-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
117
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(127 citation statements)
references
References 41 publications
(99 reference statements)
9
117
0
1
Order By: Relevance
“…By collecting dose fractionated images, the total exposure can be divided into a large number of images, each at a very small dose, enabling correction for drift resulting from beaminduced movement and also from thermal drifts of the specimen stage. The emerging consensus from a number of recent studies (10,11,15,40), which is confirmed in our present analysis, is that, on average, the largest movements tend to occur early in the exposure (Fig. S3); these early frames can be either discarded or down-weighted during image processing.…”
Section: Significancesupporting
confidence: 69%
See 2 more Smart Citations
“…By collecting dose fractionated images, the total exposure can be divided into a large number of images, each at a very small dose, enabling correction for drift resulting from beaminduced movement and also from thermal drifts of the specimen stage. The emerging consensus from a number of recent studies (10,11,15,40), which is confirmed in our present analysis, is that, on average, the largest movements tend to occur early in the exposure (Fig. S3); these early frames can be either discarded or down-weighted during image processing.…”
Section: Significancesupporting
confidence: 69%
“…S12, which shows that increasing the dose from 10 e − /Å 2 to 45 e − /Å 2 results in an ∼twofold increase in preferential damage of Asp and Glu residues compared with Asn and Gln residues, respectively. The trends we observe for preferential radiation damage of Asp and Glu residues can also be demonstrated by similar analysis of map value variations in a recently reported cryo-EM density map for Frh (10), an unrelated protein, at a resolution of 3.36 Å (Fig. S12A).…”
Section: Significancementioning
confidence: 55%
See 1 more Smart Citation
“…Radiation damage can also have a more subtle effect aside from the degradation of resolution, where damage causes protein side chains to shift, which could lead to subtle differences in the inhibitor binding position. Previous studies have shown that negative side chains appear to suffer radiation damage preferentially (Allegretti et al, 2014;Bartesaghi et al, 2014;Grant & Grigorieff, 2015), so if there are key negatively charged residues in the binding pocket then this may induce a significant movement of the inhibitor or show a binding mode which is not physiologically relevant. However, it should be noted that weak density for negative side chains can also be a feature of the electric potential map generated in the electron-microscopy experiment (Wang & Moore, 2017) and is not in all cases radiation damage.…”
Section: Challenges Faced By Electron Microscopymentioning
confidence: 99%
“…Many software packages have been developed for single particle reconstruction, including Spider (Shaikh, Gao et al 2008, Baniulis, Yamashita et al 2009), IMAGIC (Forster and Hegerl 2007), Xmipp (Sorzano, Marabini et al 2004), BSoft Belnap 2007, Heymann, Cardone et al 2008), SPARX (Hohn, Tang et al 2007) EMAN (Heymann and Belnap 2007), EMAN2 (Tang, Peng et al 2007), Relion (Scheres 2012 Furthermore state-of-the-art direct electron detectors greatly reduce the impacts of sample charging and drift on the captured image, increasingly making atomic resolution structure determination by single particle analysis (Allegretti, Mills et al 2014) a reality not only for viruses and macromolecular assemblies but also for membrane proteins in the 500kDa range (Li, Mooney et al 2013, Liao, Cao et al 2013, Lyumkis, Julien et al 2013, Bartesaghi, Matthies et al 2014, Lu, Bai et al 2014, Campbell, Veesler et al 2015 and below.…”
Section: Figure 118 Electron Image Formation Through Em and Single Pmentioning
confidence: 99%